2015
DOI: 10.1186/s12889-015-1575-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and preferences of healthy young adults regarding advance care planning: a focus group study of university students in Pittsburgh, USA

Abstract: BackgroundTo date, research and promotion regarding advance care planning (ACP) has targeted those with serious illness or the elderly, thereby ignoring healthy young adults. The purpose of this study was to explore young adults’ knowledge, attitudes, and preferences regarding advance care planning (ACP) and medical decision-making. Further, we aimed to understand the potential role of public health to encourage population-based promotion of ACP.MethodsBetween February 2007 and April 2007, we conducted six foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 29 publications
7
44
0
Order By: Relevance
“…Focus groups of undergraduate students aged 18 to 30 years found lack of information to be a major barrier to ACP discussions, with age being a moderating factor. 18 That study found that the possibility of incapacitation in the near future was difficult to consider, and therefore a barrier to advance directive completion.…”
Section: Discussionmentioning
confidence: 99%
“…Focus groups of undergraduate students aged 18 to 30 years found lack of information to be a major barrier to ACP discussions, with age being a moderating factor. 18 That study found that the possibility of incapacitation in the near future was difficult to consider, and therefore a barrier to advance directive completion.…”
Section: Discussionmentioning
confidence: 99%
“…67 Early engagement means that people can be better prepared for making decisions when they are ill, as well as ensuring that their wishes are known by staff and relatives who might have to make decisions on their behalf. Some key messages come through from the existing research:…”
Section: Palliative Care Campaigns S-31mentioning
confidence: 99%
“…One study looks at university students in the United States and recommends that an important aspect of public health is providing reliable information about advance care planning to all young people. 67 Involve the community and build coalitions. There are examples of how communities can be empowered to engage at a deep level with advance care planning and to develop plans to raise awareness in their own networks and localities.…”
Section: Palliative Care Campaigns S-31mentioning
confidence: 99%
“…Most of the health promotion strategies target people with chronic diseases or elderly and thus leave a gap in what concerns the health of young people (Kavalieratos et al, 2015). The working capacity of an individual depends on the duration and the intensity of the effort that he must carry on.…”
Section: Introductionmentioning
confidence: 99%